Fibrosis in Atrial Fibrillation – Role of Reactive Species and MPO - Friedrichs, Kai; Baldus, Stephan; Klinke, Anna (Frontiers in Physiology, 2012)
Atrial fibrosis with enhanced turnover and deposition of matrix proteins leads to inhomogeneous atrial electrical conduction and gives rise to electrical reentry circuits resulting in atrial fibrillation. The multifactorial pathogenesis of atrial fibrosis involves resident cardiac cells as well as infiltrating leukocytes, both generating and sequestering matrix metalloproteinases (MMPs), a key enzyme family involved in fibrosis. A growing body of evidence points toward an important role of reactive oxygen species (ROS) in the release and activation of pro-MMPs and the stimulation of pro-fibrotic cascades. Myeloperoxidase (MPO), a bactericidal enzyme released from activated polymorphonuclear neutrophils (PMN) is not only associated with a variety of cardiovascular diseases, but has also been shown to be mechanistically linked to atrial fibrosis and fibrillation. MPO catalyzes the generation of reactive species like hypochlorous acid, which affect intracellular signaling cascades in various cells and advance activation of pro-MMPs and deposition of atrial collagen resulting in atrial arrhythmias. Thus, inflammatory mechanisms effectively promote atrial structural remodeling and importantly contribute to the initiation and perpetuation of atrial fibrillation.